Primary Blast-Induced Changes in Akt and GSK3β Phosphorylation in Rat Hippocampus - Wang, Yushan; Sawyer, Thomas W.; Tse, Yiu Chung; Fan, Changyang; Hennes, Grant; Barnes, Julia; Josey, Tyson; Weiss, Tracy; Nelson, Peggy; Wong, Tak Pan (Frontiers in Neurology, 2017)
Traumatic brain injury (TBI) due to blast from improvised explosive devices (IEDs) has been a leading cause of morbidity and mortality in recent conflicts in Iraq and Afghanistan. However, the mechanisms of primary blast-induced TBI are not well understood. In the present study, the effects of simulated primary blast wave on the phosphorylation status of Akt and its downstream effector kinase, glycogen synthase kinase 3β (GSK3β), in rat hippocampus were investigated. Male Sprague-Dawley (SD) rats (350 – 400 g) were exposed to a single pulse shock wave (25 psi; ~7 msec duration) and sacrificed 1 day, 1 week, or 6 weeks after exposure. Total and phosphorylated Akt, as well as phosphorylation of its down-stream effector kinase GSK3β (at serine 9) were detected with western blot analysis and immunohistochemistry. Results showed that Akt phosphorylation at serine 473 was dramatically increased 1 day after blast on the ipsilateral side of the hippocampus, and this elevation persisted until at least 6 weeks post exposure. Similarly, phosphorylation of GSK3β at serine 9, which inhibits GSK3β activity, was also increased starting at 1 day and persisted until at least 6 weeks after primary blast on the ipsilateral side. In contrast, p-Akt was increased 1 week and 6 weeks on the contralateral side, while p-GSK3β was increased 1 day and 1 week after primary blast exposure. No significant changes in total protein levels of Akt and GSK were observed on either side of the hippocampus at any time points. Immunohistochemical results showed that increased p-Akt was mainly of neuronal origin in the CA1 region of the hippocampus and once phosphorylated, was translocated to the dendritic membranes of the same neurons. Finally, electrophysiological data showed that evoked synaptic N-methyl-D-aspartate (NMDA) receptor activity was significantly increased 6 weeks after primary blast, suggesting that the increased Akt phosphorylation observed in this study may be a result of enhanced synaptic NMDA receptor activation, or wise versa.